Collaborative Strategy for Marine Tourism Development Through Empowerment of Creative Economy Based MSMEs in Enhancing the Economy in Bone Bolango Regency - Mohamad Fadly Binolombangan; Kurniadi K. Hasan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze collaborative strategies in developing marine tourism through the empowerment of Micro, Small, and Medium Enterprises (MSMEs) based on the creative economy in Bone Bolango Regency. The research focuses on three main issues: collaborative strategies among stakeholders, the role of creative economy-based MSMEs in strengthening destination competitiveness, and the challenges of managing and marketing marine tourism. A descriptive qualitative method was employed, with data collected through observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation. The data were analyzed thematically, complemented by SWOT analysis, stakeholder analysis, and the Analytical Hierarchy Process (AHP) to determine strategic priorities. The findings reveal that marine tourism development in Bone Bolango has adopted a pentahelix collaboration model, where the government acts as regulator and facilitator, businesses provide services, academia generates knowledge and training, local communities manage destinations, and media serve as promotion and education agents. MSMEs play a vital role as drivers of the creative economy through handicrafts, culinary products, and tourism services based on local wisdom. However, challenges persist, including limited digital literacy, restricted access to financing, environmental threats, and competition with other marine destinations. This study proposes an adaptive collaborative strategy that integrates MSMEs into marine tourism governance, emphasizing creative economy practices to promote inclusive and sustainable development.